Optical coherence tomography derived differences of plaque characteristics in coronary culprit lesions between type 2 diabetic patients with and without acute coronary syndrome. Issue 5 (9th November 2013) - Reith, Sebastian; Battermann, Simone; Hoffmann, Rainer; Marx, Nikolaus; Burgmaier, Mathias
<x xml:space="preserve">Abstract</x> Objective To compare optical coherence tomography (OCT)‐derived plaque characteristics of coronary target lesions between diabetic patients with acute coronary syndrome (ACS) versus stable angina pectoris (SAP). Background In vivo assessment of plaque composition of coronary culprit lesions in a cardiovascular high‐risk population with diabetes mellitus is incompletely elucidated. Methods 102 diabetic patients with coronary de novo lesions were enrolled and categorized into an ACS‐group (40 patients) and a SAP‐group (62 patients) according to their clinical presentation. Assessment of clinical data, angiographic, and OCT imaging including the analysis of plaque composition and lipid content of the target lesions were performed prior to percutaneous coronary intervention and compared between the two groups. Results Plaque characteristics of patients in the ACS‐group compared with the SAP‐group showed a higher incidence of lipid‐rich plaque [33 (82.5%) vs. 25 (40.3%)], thin‐capped fibroatheroma [29 (72.5%) vs. 10 (16.1%)], macrophage infiltration [32 (80.0%) vs. 21 (33.9%)], thrombus [23 (57.5%) vs. 2 (3.2%)], and plaque rupture [27 (67.5%) vs. 2 (3.2%)] (all P < 0.001). Moreover, there was a wider lipid arc (174.5 ± 33.8° vs. 122.9 ± 43.9°), a longer lipid plaque length (6.52 ± 2.04 mm vs. 3.73 ± 2.16 mm), a greater lipid volume index (1117.2 ± 349.9 vs. 504.8 ± 379.3), and a smaller minimal fibrous cap thickness (51.52 ± 9.14 µm vs. 80.33 ± 26.71 µm) within lipid‐rich lesions of ACS patients (all P < 0.001). Conclusion Diabetic patients with ACS exhibit more vulnerable plaque features in coronary culprit lesions compared with diabetic patients with SAP. This may provide rationale for a specific therapeutic strategy either by pharmacological plaque stabilization or coronary intervention in any lesion with vulnerable plaque morphology in patients with diabetes. © 2013 Wiley Periodicals, Inc.